The Power of Dhikr: Elevating Intellectual, Emotional, and Spiritual Quotients - Irhas, Irhas; Aziz, Ahmad Amir; Satriawan, Lalu Agus (Al-Hayat: Journal of Islamic Education, 2023)
This article aims to solve problems and explain the importance of dhikr in developing intellectual, emotional, and spiritual intelligence. This research focuses on how dhikr can improve cognitive function and reduce stress and anxiety. This research method is a literature study with a psycho-sufism approach. The data were obtained from the results of previous research and also from several journal articles. Data analysis using content analysis. The results of this study indicate that dhikr increases intellectual, emotional, and spiritual intelligence, as seen in increased empathy and emotional regulation. The author explores the spiritual benefits of dhikr, arguing that it can deepen one's relationship with God and provide a sense of purpose and meaning in life. The role of dhikr in holistic development and provides insight into the potential benefits of dhikr practice. The practice of dhikr can profoundly impact a person's intellectual, emotional and spiritual well-being, making it a valuable tool for personal growth and development.